Changes in Functional Properties and In Vitro Digestibility of Black Tartary Buckwheat Starch by Autoclaving Combination with Pullulanase Treatment - Faying Zheng; Fuxin Nie; Ye Qiu; Yage Xing; Qinglian Xu; Jianxiong Chen; Ping Zhang; Hong Liu (Foods)
The processing properties of resistant starch (RS) and its digestion remain unclear, despite the widespread use of autoclaving combined with debranching in its preparation. In this study, the physicochemical, rheological and digestibility properties of autoclaving modified starch (ACB), autoclaving–pullulanase modified starch (ACPB) and native black Tartary buckwheat starch (NB) were compared and investigated. The molecular weight and polydispersity index of modified starch was in the range of 0.15 × 104~1.90 × 104 KDa and 1.88~2.82, respectively. In addition, the SEM results showed that both modifications influenced the morphological characteristics of the NB particles, and their particles tended to be larger in size. Autoclaving and its combination with pullulanase significantly increased the short-range ordered degree, resistant starch yield and water- and oil-absorption capacities, and decreased the syneresis properties with repeated freezing/thawing cycles. Moreover, rheological analysis showed that both ACB and ACPB exhibited shear-thinning behavior and lower gel elasticity as revealed by the power law model and steady-state scan. The degradation of starch chains weakened the interaction of starch molecular chains and thus changed the gel network structure. The in vitro digestion experiments demonstrated that ACB and ACPB exhibited greater resistance to enzymatic digestion compared to the control, NB. Notably, the addition of pullulanase inhibited the hydrolysis of the ACB samples, and ACPB showed greater resistance against enzymatic hydrolysis. This study reveals the effects of autoclaving combined with debranching on the processing properties and functional characteristics of black Tartary buckwheat starch.